PREVALENCE OF DENTOALVEOLAR ANOMALIES IN 6-16 YEARS CHILDREN ACCORDING TO RETROSPECTIVE DATA ANALYSIS - Sh, Olimov S.; S.A, Gaffarov; R.K, Yakubov; A.A, Saidov; B.B, Badriddinov (International Journal of Psychosocial Rehabilitation, 2020)
It was studied the prevalence of dental anomalies at 6-9 years’ children in Bukhara region by carried out a comparative retrospective analysis of 831 cases histories of patients with various occlusion abnormalities for 2009- 2019 years. Distal occlusion and orofacial dysfunctions was diagnosed at 47,1% of all children. Number of children without orofacial dysfunctions and dentoalveolar anomalies remains almost unchanged (p> 0,10), whereas a share of children with dentofacial anomalies and deformities were increased from 16,5% to 72,6% (p